Kinerja Dosen Di Unit Pelayanan Terpadu Laboratorium Dasar Dalam Pelayanan Akademik Di Universitas Tadulako - Nurhayati Ambo; Suasa; Nurhannis (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to determine the performance of lecturers in the basic laboratory integrated service unit in academic services at tadulako University Palu. The results of the research show that the performance of lecturers at the basic laboratory integrated service unit in academic services at tadulako University Palu has not run optimally, this is because of the 4 aspects studied, there are 3 aspects that have not worked well, namely aspects of effectiveness, responsibility and discipline and only 1 the aspect that works well is the initiative aspect. The research suggestion is that to improve the performance of basic laboratoty lecturers, it is necessary to build a performance concept to improve the quality of academic services at tadulako University Palu, especially at the basic laboratory integrated service unit adjusted to the organization and governance that apply in the basic laboratory integrated service unit. To improve the quality of lecturer performance at the basic laboratory integrated service unit at Tadulako University Palu, the fooowing steps must be taken: it is necessary to create a workshop on the academic service system which is attended by basic laboratory lecturers at tadulako University Palu, it is necessary to give academic sanctions to lecturers who are in effective in their work, such as is no longer scheduled for the next semester after previously being evaluated as irresponsible in carrying out academic services, it is necessary to review the amount and time of honorarium payments that apply in the basic laboratory integrated servive unit Tadulako University Palu.